FACTORS AFFECTING NURSE’S PARTICIPATION IN MAKING HEALTH POLICY OF (PUNJAB) PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Nurses are the largest healthcare profession and are well-positioned to contribute to the development of health policy. Nevertheless, in most health systems, their engagement in policymaking is minimal. This research investigated the determinants that influence nurses' participation in the health policymaking process in Punjab, Pakistan.A cross-sectional descriptive study design was employed. A purposive sample of 101 driven leaders and administrators in nursing in Punjab, including public health sector directors, Deans/Principals, Chief Deputy Nursing Superintendents, and nursing superintendents, was selected. The data were collected using a validated questionnaire that was modified based on existing measures of factors influencing nurses' political involvement. Data analysis involved both descriptive and inferential statistics.The research findings indicated that several factors significantly influence the involvement of nurses in Health policy. Not many nurses demonstrated a lack of knowledge about the policy processes, and they firmly believed that nurses should have a greater role in policymaking. The available professional experience and favorable organizational environment were found to have a positive impact on nursing's exposure to policy work.The findings of this study highlight the contributions of nurses to the policy advocacy landscape and inform on how the health policymaking process may be improved in Pakistan. The results suggest that nurses should be provided with targeted educational interventions, organizational support, and system-level changes to optimise their contributions to health policy development.